Laparoscopic orchidopexy and its outcome in the management of nonpalpable testis - Prasad, Dinesh; Jivani, Savan (International Surgery Journal, 2020)
Background: Management of impalpable testis represents a significant diagnostic and operative challenge. The aim of this work was to present the superior value of laparoscopy as a single tool for the diagnosis and treatment of impalpable testis. Methods: 51 patients with 58 nonpalpable were included in our study. Study design was case series. We have conducted this study at Surat Municipal Institute for Medical Education and Research, Surat. For each patient laparoscopy orchidopexy was performed and either testis or blind ending cord structure are searched for. The testis either brought down to the scrotum or removed depending on the condition. The patients were followed up for 12 months. Results: On diagnostic laparoscopy the number of testis found normal 54, followed by 3 hypoplastic and 1 atrophic. There were 8 testis found to be present at high intraabdominal (>2 cm from deep ring), 46 were present at low intra-abdominal (<2 cm from deep ring), intracanalicular 4. Postoperative complication included minor wound infection in one patient, none of them were diagnosed scrotal hematoma, port site hernia, and testicular atrophy. Conclusions: Laparoscopy seems to offer a safe and reliable diagnostic and therapeutic option to patients with nonpalpable testis. Intraabdominal dissection allows more testis to be brought down to scrotum. Laparoscopy clearly demonstrate the anatomy and provide visual information upon which a definitive decision can be made.